Domiciliary cockroaches found in restaurants in five zones of Kuala Lumpur federal territory, peninsular Malaysia - Jeffery, J.; Sulaiman, S.; Oothuman, P.; Vellayan, S.; Zainol-Ariffin, P.; Paramaswaran, S.; Razak, A.; Muslimin, M.; Kamil-Ali, O.B.; Rohela, M.; Abdul-Aziz, N.M. (2012)
The following domiciliary cockroaches were collected from restaurants in five zones of Kuala Lumpur Federal Territory, Malaysia using IL glass beaker traps baited with ground mouse-pellets: Periplaneta americana (Linnaeus) (n = 820), Periplaneta brunnea Burmeister (n = 46), Blattella germanica (Linnaeus) (n = 12504), Supella longipalpa (Fabricius) (n = 321), Symploce pallens Stephens (n = 29) and Neostylopyga rhombifolia (Stoll) (n = 5). The following bacteria were isolated from 10 cockroach specimens: Enterobacter cloacae, Klebsiella pneumoniae ssp. pneumoniae, Klebsiella pneumoniae ssp. rhinoscleromatis and Serratia liquefaciens from 5 B. germanica; Acinetobacter calcoaceticus var. anitratus, Citrobacter diversus/amalonaticus, Escherichia vulneris and K.p. pneumoniae from 3 P brunnea; and Citrobacter freundii, Enterobacter agglomerans 4, Escherichia adecarboxylate, E. vulneris, K. p. pneumonia, K p. rhinoscleromatis and Proteus vulgeris from 2 P americana.